PENGARUH PENAMBAHAN SERAT KEPOMPONG ULAT SUTRA (Bombyx moriL.) TERHADAP KEKUATAN TARIK DIAMETRAL RESIN KOMPOSIT FLOWABLE - Murdiyanto, Dendy (Muhammadiyah University Press, 2020)
Composite flowable is composite that have low viscocity and have amount of filler 60% from the total weight. The low amount of the filler make resin composite flowable have lower mechanical properties then the conventional resin composite. One of the important mechanical propeties is the diametral tensile strength, the force that make a material elongated and stretch before the material finally break. The additional of fiber can increase the toughness of tensile. Silkworm fiber (bombyx mori L.) actually have high tensile strength until 600Mpa. The objective of this research is to determine the effect of adding cocoon silkworm fiber on flowable composite resin diametral tensile strength and to determine the effect of adding cocoon silkworm fiber on the increase of diametral tensile strength. The study design was post-test-only control design which measures the diametral tensile strength of flowable composite resin with and without the addition of silkworm cocoons fibers. The object for the research was flowable composite resin groups as 32 samples were divided into 2 groups: control group and treatment group. Independent T-Test result showed that there was significant means difference ( 0.05) with 43,086 MPa for the treatment group and 38,504MPa for the control group. Conclusion of this study was the additional of silkworm cocoons fiber have influence to the diametral tensile strength. The addition of silkworm cocoon fiber increase the diametral tensile strength of flowable compositeÂ resin.Â Â